THE RESEARCH OF MUTUAL INFLUENCE OF COMPRESSION AND ENCIPHERING PROCEDURES FOR INFORMATIVE MESSAGES - Юдін, О.; Курінь, К. (Science-based technologies, 2010)
The analysis of dependence of efficiency of methods of data protection from statistical descriptions of messages is provided. The entropy characteristics of messages are considered: the entropy of plaintext of related to the ciphertext, which characterize the unreliability of cryptosystem; entropy of the uncompressed message, which determine its surplus. The mathematical model of procedure of research of influence of combination of procedures of compression and enciphering on firmness of plaintext and degree of compression is created. The formed model is realized with the programmatic facilities of Cryptool. The statistical characteristics of initial and modified texts are calculated.